2008
DOI: 10.1177/1420326x08089364
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between PMV and Dissatisfaction on the Basis of the ASHRAE and the McIntyre Scale — Towards an Improved Concept of Dissatisfaction

Abstract: This paper proposes a concept of dissatisfaction that is based on the correlation between the McIntyre and the ASHRAE votes of the ASHRAE RP-884 Adaptive Model Project — Data. The correlation shows that people who are voting with ASHRAE ·2 or beyond are not necessarily dissatisfied (which is the basic assumption of the classical PPD concept) and vice versa, that people who are voting between -1 and 1 are not necessarily satisfied with their thermal environment. The data set was divided into several factors (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 2 publications
0
16
0
2
Order By: Relevance
“…The mean radiant temperature in the older people's centers was $4% below the air temperature (R ¼ 0.89, p50.0001, t-test). For the older people's centers (sites [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], thermal votes of 403 occupants (303 females and 100 males) were collected; 384 out of these 403 occupants were older people (age ! 60 years) and 19 were staff at the centers.…”
Section: Field Study Of Thermal Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean radiant temperature in the older people's centers was $4% below the air temperature (R ¼ 0.89, p50.0001, t-test). For the older people's centers (sites [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], thermal votes of 403 occupants (303 females and 100 males) were collected; 384 out of these 403 occupants were older people (age ! 60 years) and 19 were staff at the centers.…”
Section: Field Study Of Thermal Environmentsmentioning
confidence: 99%
“…Thermal environment relates to the perception of satisfaction of the subject and is primarily dependent on the air temperature, the radiant temperature, the air velocity, and the relative humidity of the perceived environment to the person at his/her metabolic rate and the kind of clothing he/she is wearing [10]. Studies of thermal sensation reported linear regressions of the Predicted Mean Vote (PMV) on a 7-point ASHRAE scale of thermal sensation to the operative temperature or the effective temperature in order to derive the neutral temperature, which was the temperature at which the occupants felt ''neutral'' and would not vote either on the warm side or the cool side [11]. However, the PMV index is generally applied to evaluate thermal environments so that the results can be compared with those from other investigations [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, thermal sensations outside of the three central categories of the ASHRAE 7-point scale of thermal sensation do not necessarily reflect discomfort for a substantial number of persons. Von Grabe and Winter 52 showed that people who are voting -2 and +2 on the ASHRAE 7-point scale of thermal sensation or beyond are not necessarily dissatisfied. Also, people who are voting between -1 and 1 are not necessarily satisfied with their thermal environment either 52 .…”
Section: Semantics and Thermoneutrality As An Idealmentioning
confidence: 99%
“…Von Grabe and Winter 52 showed that people who are voting -2 and +2 on the ASHRAE 7-point scale of thermal sensation or beyond are not necessarily dissatisfied. Also, people who are voting between -1 and 1 are not necessarily satisfied with their thermal environment either 52 .…”
Section: Semantics and Thermoneutrality As An Idealmentioning
confidence: 99%
“…Different area can have different thermal comfort model and a subject's thermal sensation would be different according to individual, race, climate, habits and customs, etc. Researches on adaptive thermal comfort studies have been carried out and thermal comfort standards and comfortable temperature could be variable in different countries or areas as the literature [6][7][8][9][10][11][12][13][14][15] shows. The thermal environment in ship cabins may be different from that in land buildings and the thermal conditions in land buildings would not reflect the real conditions in ship cabins.…”
mentioning
confidence: 99%